The Effect of Adding Torrefied Fraction to Biomass Pellet from Corn Stover: Physical Properties and Fuel Qualities. (2019) - Phonlayut, T.; Soykeabkeaw, N.; Intatha, U.; Tawichai, N.
Abstract: Biomass pellet is one of a superior renewable energy. This work aims to improve efficiency of biomass pellet from corn residues, which are abundantly available after harvesting in Thailand by adding a torrefied fraction. Torrefaction treatment (225 – 300 °C in nitrogen gas atmosphere for 30 min) was applied to corn stover (only leaves and stalks) and then mixed with the biomass in various ratios (i.e., 100:0, 90:10, 20:80, 0:100). The pellets were formed using uniaxial pressing with an 8 mm diameter die at pressure of 80 MPa. The physical properties of pellets such as bulk density, expansion ratio, moisture content, and durability are measured. The ash content and heat value are determined using standard laboratory methods.